Identification learning skills on the young prisoners in correctional institution - Gusni Dian Suri; Mudjiran Mudjiran; Syahniar Syahniar (Fakultas Ilmu Pendidikan UNP)
Young prisoners need non-formal education in order to achieve the targeted teenager's future, because young prisoners have the right to carry out educational. The purpose of this study was to describe learning skills of the young prisoners in correctional institution adolescent Tanjung Pati Lima Puluh Koto. An analyze of the data used instruments learning skills of the young prisoners to 23 teenagers and analysis used is presentation. The research finding showed that learning skills of young prisoners at a medium level. The implication of this research is to identification learning skills young prisoners. In order, the results of this study could be data to assist the prisoners for solving their problems in learning skills, in developing a product to improve learning skills of the young prisoners.